Her favorite mistake - Harlen, Brenda (Harlen, Brenda. Match made in Haven, 2024)
"Natalya Vasilek is finally content with her life. The former navy pilot has a good job in Haven, Nevada, reliable friends and a hunky colleague who indulges with her in the occasional hookup. The more time Nat spends with Kevin Dawson, the more she finds herself wanting to believe in forever. But a career-ending injury that stole her chance at a family has made her wary of trusting that anything can last. Kevin wants his part-time lover to be his full-time partner. But Nat refuses to even discuss the possibility. If Kevin can find a way to show Nat that he longs to build a life with her, maybe he can convince her that friends with benefits can find happily-ever-after?" --